Neoplasma Ovarium Kistik - Muhammad Syifa Albi Nasution (Calory Journal Medical Laboratory Journal, 2025)
Ovarian cysts are ovarian tumors that can be either neoplastic or non-neoplastic, with varying characteristics in terms of size, consistency, and malignancy. During pregnancy, the most commonly encountered types include dermoid cysts, endometriomas, and lutein cysts. The actual prevalence of ovarian cysts is difficult to determine as most cases remain undiagnosed, with studies indicating that around 4% of women will experience hospitalization due to ovarian cysts by the age of 65. Evaluation of ovarian masses requires a multidisciplinary approach, including ultrasonography and tumor markers to assess the likelihood of malignancy. This case involves a 45-year-old woman who presented with lower abdominal pain, bloating, and significant weight loss. Ultrasound findings revealed a cystic mass with solid components, suspected to be a malignant ovarian cyst. The provisional diagnosis was cystic ovarian neoplasm with suspected malignancy, and the patient underwent laparotomy with right salphingo-oophorectomy. Post-surgery, the patient's condition improved, though she continued to experience pain at the surgical site. Ovarian cysts can present with nonspecific symptoms and are often found incidentally. Further evaluation is necessary to assess malignancy and determine appropriate treatment. Surgical intervention is required for cases with suspected malignancy, especially in cysts with solid masses and large size.